Textbook of small animal emergency medicine - Drobatz, Kenneth J.; Hopper, Kate; Rozanski, Elizabeth A.; Silverstein, Deborah C. (Wiley-Blackwell, 2019)
"Textbook of Small Animal Emergency Medicine offers an in-depth understanding of emergency disease processes and the underlying rationale for the diagnosis, treatment, monitoring, and prognosis for these conditions in small animals"--Publisher's description